Peningkatan Layanan Angkutan Umum Melalui Aplikasi Pencarian Angkutan Umum Berbasis IoT - Wisnu Wijayanto, Pikir; Qana’a, Mutia; Bayu Rima Aditya, Bayu (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
The city of Bandung has implemented the Smart City concept as part of efforts to improve the quality of life and efficiency of community administration. However, public transportation in the city of Bandung still has several problems, including reduced use of city transportation due to the increase in crime on public transportation, lack of information regarding public transportation lines and routes, and erratic departure times. To overcome this problem, community service activities were carried out in the form of developing an IoT-based public transportation search application using BLE. This application provides an emergency call feature to deal with crime in public transportation and ensure passenger safety, helping passengers track the location of public transportation more easily so that it will provide information such as public transportation routes and public transportation departure times. Based on the evaluation results from KOBUTRI representatives, it can be concluded that in general this community service program has had a positive impact on all participants. Several suggestions and input also emerged from filling out the questionnaire, including: equipped with tariffs, the payment system can use e-money cards, and hopefully this program and its application can run in 2024. With the successful development of an IoT-based public transport search application in the city Bandung, an important step has been taken to overcome public transportation problems. This application is expected to improve administrative efficiency and people's quality of life through public transport innovation.